Histone methyl-transferases and demethylases in the autophagy regulatory network: the emerging role of KDM1A/LSD1 demethylase. Issue 2 (1st February 2019) - Ambrosio, Susanna; Ballabio, Andrea; Majello, Barbara
ABSTRACT: Macroautophagy/autophagy is a physiological mechanism that is essential for the maintenance of cellular homeostasis and stress adaptation. Defective autophagy is associated with many human diseases, including cancer and neurodegenerative disorders. The emerging implication of epigenetic events in the control of the autophagic process opens new avenues of investigation and offers the opportunity to develop novel therapeutic strategies in diseases associated with dysfunctional autophagy-lysosomal pathways. Accumulating evidence reveals that several methyltransferases and demethylases are essential regulators of autophagy, and recent studies have led to the identification of the lysine demethylase KDM1A/LSD1 as a promising drug target. KDM1A/LSD1 modulates autophagy at multiple levels, participating in the transcriptional control of several downstream effectors. This review summarizes our current understanding of the role of KDM1A/LSD1 in the autophagy regulatory network.